Manufacturing of E-Glass/Epoxy Composite LSU-03 Propeller Using Hand Lay-up Method - A Z Dwi; H Syamsudin (AVIA, 2020)
Hand lay-up method is frequently used by small companies. It is due to its flexibility and low-cost considerations. One of the qualities problems that normally arises is the product unevenness. This study was carried out to analyse this variation on manufacturing E-glass/epoxy plates specimen and propeller product. Void and fibre volume fraction of manufactured plates are measured based on ASTM-D2734. Propellers of LSU-03 aircraft were manufactured and analysed to find out the uniformity of the product in terms of its mass and size. To determine product compatibility with the design, the geometry and the thickness were measured at several points of propeller. In addition to this, a balancing process is carried out to find out the mass balance point.